Seven-year performance of biosand filters in rural Rwanda - Bethesda O'Connell; Charles Olomofe; Megan Quinn; Deborah Slawson; Theoneste Ntakirutimana; Phillip Scheuerman (Journal of Water, Sanitation and Hygiene for Development, 2023)
Waterborne diseases remain a significant public health problem, and biosand filters (BSFs) are a common household water filtration method for improving drinking water quality to prevent diseases. The purpose of this study was to evaluate the effectiveness of BSFs over time in a rural Rwandan community. Sixteen BSFs were installed – eight in 2015 and eight in 2018. Influent and effluent samples were tested with Colilert Presence/Absence kits in 2015, 2017, 2018, 2019, and 2022. About 92.9% of filters were still in use in July 2022, but only 64.3% were functioning well, and 50% of effluent samples tested positive for fecal coliforms. A Kruskal–Wallis H test showed no statistically significant difference in effluent percent positive for fecal coliforms by filter age [χ2 (1) = 4.00, p = 0.41]. Recorded observations about each filter, such as rusted diffuser plates, may be useful for understanding the need for maintenance over time. HIGHLIGHTS No statistically significant difference in the percent positive fecal coliforms by filter age (1–7 years), but 50% of effluent samples were positive for fecal coliforms at the last sampling.; High community adoption rate with 92.9% in continued use after seven years.; Maintenance such as diffuser plate replacement may be needed over time for biosand filters to remain effective.;